Insight, positive and negative symptoms, hope, depression and self-stigma: a comprehensive model of mutual influences in schizophrenia spectrum disorders. (24th July 2013) - Schrank, B.; Amering, M.; Hay, A. Grant; Weber, M.; Sibitz, I.
Abstract : Aims: Insight, positive and negative symptoms, hope, depression and self-stigma are relevant variables in schizophrenia spectrum disorders. So far, research on their mutual influences has been patchy. This study simultaneously tests the associations between these variables. Methods: A total of 284 people with schizophrenia spectrum disorders were assessed using the Schedule for the Assessment of Insight, Positive and Negative Syndrome Scale, Integrative Hope Scale, Centre for Epidemiological Studies Depression Scale and Internalized Stigma of Mental Illness scale. Path analysis was applied to test the hypothesized relationships between the variables. Results: Model support was excellent. Strong and mutual causal influences were confirmed between hope, depression and self-stigma. The model supported the assumption that insight diminishes hope and increases depression and self-stigma. While negative symptoms directly affected these three variables, reducing hope and increasing depression and self-stigma, positive symptoms did not. However, positive symptoms diminished self-stigma on a pathway via insight. Conclusions: This study provides a comprehensive synopsis of the relationships between six variables relevant for schizophrenia spectrum disorders. Research implications include the need to investigate determinants of consequences of insight, and the sequence of influences exerted by positive and negative symptoms. Clinical implications include the importance of interventions against self-stigma and of taking a contextualized approach to insight.